Retailing traditional African vegetables in Zambia - Justus Ochieng; Ramu Govindasamy; Fekadu F Dinssa; Victor Afari-Sefa; James E Simon (Agricultural Economics Research Review, 2023)
In sub-Saharan Africa, including Zambia, rising awareness of the nutrition and health benefits of traditional African vegetables (TAVs) has raised demand over the past decade. TAVs compete with conventional vegetables in most retail outlets such as supermarkets and small food stores. Yet, there is little information on the retail structure of organic traditional vegetables. This study sought to identify the trading structure of organic TAVs; the determinants of retailers’ decision to sell these vegetables and the major bottlenecks to the growth of TAV retailing. Results indicated that it was the expected profits and consumer concerns over food safety that influence the retailers’ decision to sell organic TAVs.